Memoirs of a geisha [videorecording (DVD)] - Marshall, Rob; Zhang, Ziyi, 1979-; Watanabe, Ken, 1959-; Yeoh, Michelle, 1963-; Golden, Arthur, 1957- (Sony Pictures Home Entertainment, 2007)
In 1929, an impoverished fishing village father sells his nine-year-old daughter, Chiyo, to a geisha house in Kyoto's Gion district and she becomes subjected to cruel treatment from the owners and the head geisha Hatsumomo. As she grows older, her stunning beauty attracts the vindictive jealousy of Hatsumomo. She is rescued by and taken under the wing of Hatsumomo's bitter rival, Mameha. Under Mameha's mentorship, Chiyo becomes the geisha named Sayuri, trained in all the artistic graces and social skills a geisha must master. As a renowned geisha, she enters a society of wealth, privilege, and political intrigue. With the onslaught of World War II, Japan and the geisha's world are forever changed.